Influence of landscape structure on carbon storage in agroforestry systems with cacao and silvopastoral systems in the Colombian Amazon - Jenniffer Tatiana Díaz-Cháux; Alexander Velasquez-Valencia; Fernando Casanoves (PLoS ONE, 2025)
In the Colombian Amazon region, agricultural and livestock activities lead to changes in land use, transforming complex and heterogeneous natural landscapes into landscapes characterized by a matrix of pastures and forest fragments with low connectivity. These agroforestry landscapes play a crucial role in biodiversity conservation and the carbon cycle. The objective of this research was to determine the influence of landscape structure and spatial configuration in cacao-based agroforestry systems (SAFc) and silvopastoral systems (SSP) on carbon storage in the Colombian Amazon. The study was conducted across eight mosaics of rural production landscapes in the Amazon region, each consisting of a 1 km² grid where vegetation covers were classified, and landscape metrics were quantified. A total of 78 plots of 0.1 ha were established in 44 cover patches within the SAFc and SSP mosaics, and dasometric variables were measured to inventory carbon deposits in aboveground biomass, root biomass, litter, and herbaceous vegetation. It was estimated that, in the Colombian Amazon, the studied SAFc and SSP systems store an average of 15.20 Mg C ha‐ 1 in their biomass. Carbon storage was positively correlated with landscape aggregation metrics and spatial configuration within the system mosaics. Mosaics with patches of symmetrical shapes and lower irregularity, exhibiting greater contiguity, showed higher biomass and carbon storage. Therefore, productive landscapes with complex and connected mosaics enhance the provision of regulatory ecosystem services through carbon storage. Restoration efforts in fragmented areas should be managed at the landscape level by expanding the area of planting patches, establishing patches with regular geometric configurations, and improving connectivity among patches of the same type.